Knowledge Transfer Program (KTP) from International Islamic University Malaysia (IIUM): leveraging MyEntrepreneur2Cloud and Network of Mosque (NoM) to obliterate poverty in Malaysia - Adrian, Qadhli Jafar; Madani, Muhammad Fauzi; Mohamed Hassan El Hoby, Hany; Ahmad Dahlan, Abdul Rahman (2013)
Poverty is both a social and an economic problem. Eradicating poverty has become the main concern in most developed countries. In this paper, the authors elaborate on how Knowledge Transfer Program (KTP) from International Islamic University Malaysia (IIUM) would support Malaysia to obliterate the poverty. The authors proposed an integrative and collaborative mechanism namely MyEntrepreneur2Cloud which leverage on Quadruple Helix Model (QHM) and Whole of Government (WoG) concepts. Network of Mosque (NoM) concept also introduced in this paper to assist the proposed mechanism in the delivering processes. By leveraging to MyEntrepreneur2Cloud and Network of Mosque (NoM), the authors expect that the poverty in Malaysia can be obliterated.